Pengaruh Edukasi Tentang Bantuan Hidup Dasar (BHD) Terhadap Pengetahuan Anggota PMR SMAN 2 Kota Bengkulu - Hanisyah Herti Dwisari; Ravika Ramlis; Meri Epriana Susanti (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The incidence of cardiac arrest in Indonesia is recorded in the IHME (Institute for Health Metrics and Evaluation) cases of death due to cardiac arrest as many as 251.09 deaths per 100,000 people in 2023, this number increased by 1.25% compared to 2022 which was 247.99 deaths per 100,000 population. The prevalence of cardiac arrest in Bengkulu Province from doctor's diagnosis in the population of all ages was 6,571 sufferers (Indonesian Health Survey, 2023). The purpose of the study was to determine the effect of education on basic life support (BHD) on the knowledge of PMR members of SMAN 2 Bengkulu City. This study used a pre-experimental one group pretest posttest design with a sample of 20 respondents. Data collection was carried out using pre-test and post-test questionnaires on respondents. Based on the results of univariate analysis, it is known that the level of knowledge of PMR members of some of the respondents (75%) is classified as less, namely 15 respondents and after the intervention, the level of knowledge of PMR members of most of the respondents (55%) is in the sufficient category, namely 11 respondents, and almost half of the respondents (35%) are in the good category, namely 7 respondents. The bivariate analysis of this study uses the Wilcoxon test to determine the effect of basic life support (BHD) education. The results of the Wilcoxon test show that the p value is 0.000 (p <0.05) which means that there is an effect of basic life support (BHD) education on the knowledge of PMR members of SMAN 2 Bengkulu City. Researchers suggest that educators implement basic life support (BHD) education to improve student knowledge.